Mengukur Kekuatan Komisi Antikorupsi - Winarta, Frans Hendra (Pelita Harapan University, 2001)
The Indonesia governments first attempt to curb corruption occurred after the 1955 election. It resulted in the arrest of those involved, including civil servants and a minister. In June 1968, Suharto assigned the task of tackling corruption cases to the Team Pemberantasan Korupsi (Corruption Eradication Team) which was, how ever, Â ineffective because its efforts were blocked by influential men in the regime. Student protest in January 1970 and press criticism of government corruption resulted in the appointment of a special Commission on four elder statesmen (Komisi IV) by Presiden Suharto to review the problem of corruption within the civil service and to make recommendation for improvement. This commission presented seven reports on those agencies and area that were judged to vulnerable to corruption to Presiden Suharto from February to June 1970. Perhaps the most important consequence of these reports was the passing of the Preventive Against Corrupt Criminal Acts Bill in 1971 which than to be Corrupt Criminal Acts Eradication Act No. 3/ Year 1971. Previously, corruption was dealt with as a crime under the criminal code. Though there was corrupt criminal acts eradication law, corruption remained a serious problem and became institutionalized in Indonesia (WWW. Asiamedia. ucla. edit). In 1999, UU (Act) No. 3/ Tahun 1971 was replaced by UU (Act) No. 31/ Tahun 1999 and according to section 43 (I) ofUU (Act) No. 31/ Tahun 1999 Indonesia should have Commission of Corrupt Criminal Acts Eradication within two years after the law effective. What is Commission of Corrupt Criminal Acts Eradication? This is the story.Â